O086 Genomic analysis of response to neoadjuvant chemotherapy in oesophageal adenocarcinoma. (22nd July 2022) - Breininger, SP; Izadi, F; Sharpe, B; Secrier, M; Gibson, J; Walker, R; Rahman, S; Devonshire, G; Lloyd, M; Walters, Z; Fitzgerald, R; Rose-Zerilli, M; et al.
Abstract: Introduction: Oesophageal adenocarcinoma (OAC) is the ninth most common cancer worldwide with a mortality of over 500, 000 deaths yearly. Neoadjuvant chemotherapy (NAC) followed by surgery is the standard of care (SOC) for locally advanced OAC. Although almost all patients receive chemotherapy as SOC, fewer than 20% obtain a clinically meaningful response and benefit before surgery. The OAC genome is complex and heterogeneous between patients, and it is not yet understood whether specific mutational patterns result in chemotherapy sensitivity or resistance. Methods: To identify associations between genomic events and response to NAC in OAC, a comparative genomic analysis was performed in 65 patients using whole-genome sequencing. We defined response to NAC using Mandard Tumour Regression Grade TRG), with responders classified as TRG1-2 (n=27) and non-responders classified as TRG4- 5 (n=38). Results: We report a higher non-synonymous mutation burden in responders (median 2.08/Mb vs 1.70/Mb, P=0.036) and elevated copy number variation (CNV) in non-responders (282 vs 136/patient, P <0.001). We identified CNVs unique to each group, with cell cycle (CDKN2A, CCND1 ), c-Myc ( MYC ), RTK/PIK3 ( KRAS, EGFR ) and gastrointestinal differentiation ( GATA6 ) pathway genes being specifically altered in non-responders. Of particular interest was the identification of the Neuron Navigator-3 ( NAV3 ), a known tumour suppressor downstream of EGFR, which was mutated exclusively in 22% of non-responders. Conclusion: We characterise genetic features and mutations that are uniquely associated with response to NAC. We envision a treatment pipeline that incorporates driver mutation profiling in OAC, combining response prediction with targeted therapies enhancing response to NAC and improving survival outcomes. Take-home message: Developing a method of determining an OAC patient's response to neoadjuvant chemotherapy before treatment is administered is desperately needed and will improve patient outcome and quality of life. We identified a number of aberrations in the genome that were unique to non-responders to chemotherapy compared to responders, particularly a known tumour suppressor gene namely Neuron Navigator-3, suggesting that these events may contribute to chemoresistance in these patients. Our work characterises pre-existing genomic alterations that have potential as biomarkers for resistance or sensitivity to NAC.